Will the Oxford English Dictionary Be More 'European' After its First Comprehensive Revision since its First Edition of 1884-1928? - John Simpson (Miscelánea: A Journal of English and American Studies, 2004)
This paper asks a puzzling question in its title, and then looks at various aspects of the current revision of the Oxford English Dictionary (OED; Third Edition, 2000-) in search of answers. After a brief account of the history of the dictionary from the nineteenth century up to the present day, it examines some new words which have entered English from the languages of continental Europe, and then reviews some of the older words in English, which entered English at a much earlier period. Aspects of a shared European culture emerge through the exchange of vocabulary (both imports into and exports from English), and the paper highlights types of text (including Internet sources) which are important in plotting this language change.
Keywords: dictionaries; lexicography; philology; Oxford English Dictionary; language change; neologisms; loanwords; etymology; Internet; Anglicisms; modern European languages